2017
DOI: 10.1021/acs.accounts.6b00651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mineral Dissolution/Precipitation and CO2 Exsolution on CO2 transport in Geological Carbon Storage

Abstract: Geological carbon sequestration (GCS) in deep saline aquifers is an effective means for storing carbon dioxide to address global climate change. As the time after injection increases, the safety of storage increases as the CO transforms from a separate phase to CO(aq) and HCO by dissolution and then to carbonates by mineral dissolution. However, subsequent depressurization could lead to dissolved CO(aq) escaping from the formation water and creating a new separate phase which may reduce the GCS system safety. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…Dissolution/precipitation reactions (not only induced by gas) modify hydrological properties such as the porosity, reactive surface area, and permeability at the pore-and core-scales (Gouze and Luquot 2011;Xu et al 2017). Moreover, CO 2 injection into a heterogeneous medium may create wormholes, depending on the relationship between geochemical reactivity and fluid motion (Snippe et al 2017).…”
Section: Feedback On Fluid and Matrix Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolution/precipitation reactions (not only induced by gas) modify hydrological properties such as the porosity, reactive surface area, and permeability at the pore-and core-scales (Gouze and Luquot 2011;Xu et al 2017). Moreover, CO 2 injection into a heterogeneous medium may create wormholes, depending on the relationship between geochemical reactivity and fluid motion (Snippe et al 2017).…”
Section: Feedback On Fluid and Matrix Propertiesmentioning
confidence: 99%
“…These relationships are actually more complex than this relatively simple description, especially at small scales. For example, Xu et al (2017) demonstrated that mineral dissolution can enlarge pore throats, increase porosity and permeability, decrease capillary pressure, and influence relative permeability due to the injection of dissolved CO 2 in a Chaunoy sandstone core from the Paris Basin. A depressurization test revealed that gas exsolution and mineral precipitation may occur.…”
Section: Feedback On Fluid and Matrix Propertiesmentioning
confidence: 99%
“…Henry's law was used to model CO 2 solubility into brine. The effect of CO 2 solubility into brine was included since it could be considered an intermediate trapping mechanism . Also, PVT properties of brine (such as brine density) are a function of CO 2 solubility .…”
Section: Modeling Approachmentioning
confidence: 99%
“…The effect of CO 2 solubility into brine was included since it could be considered an intermediate trapping mechanism. 40,41 Also, PVT properties of brine (such as brine density) are a function of CO 2 solubility. 41 The amount of CO 2 trapped as residual gas in the aquifer was determined by the Land model.…”
Section: Code Descriptionmentioning
confidence: 99%
“…However, significant developments are yet to arrive. Novel approaches for studying the basic mineral carbonation methods were suggested as there is a scope for advancement, including additive recovery, which has not been investigated thoroughly (Bobicki et al, 2015;Centi and Perathoner, 2014;Jafari et al, 2017;Li et al, 2013;Olajire, 2013;Paul et al, 2017;Xu et al, 2017). (Haug et al, 2010;Zhao et al, 2010) HNO3 extraction HNO3 used to extract reactive components…”
Section: Comparison Of Various Sequestration Routesmentioning
confidence: 99%